Implementasi Penggunaan Media Pembelajaran Pendidikan Agama Islam Untuk Meningkatkan Motivasi Belajar Siswa Kelas V UPTD SDN 185 Inpres Salomatti Kabupaten Maros - Sahrul; Abd. Azis Muslimin; Wahyudin (Advances In Education Journal, 2025)
This study aims to describe the implementation of instructional media in Islamic Religious Education (PAI) subjects to enhance the learning motivation of fifth-grade students at UPTD SDN 185 Inpres Salomatti.The research employed a case study approach with a qualitative method. Data were collected through interviews, observations, and documentation, involving the principal, the Islamic Religious Education teacher, and fifth-grade students as the primary informants. The findings reveal that: (1) The implementation of instructional media in PAI learning for fifth-grade students at UPTD SDN 185 Inpres Salomatti has been carried out fairly well, providing significant benefits for both teachers and students. (2) Student learning motivation remains at a moderate level but tends to increase when teachers use engaging media such as animated videos, images, and technology-based quizzes. (3) Supporting factors include teachers’ readiness to use technology, support from the school through Teacher Working Group (KKG) activities, and students’ enthusiasm for the media applied. Meanwhile, inhibiting factors include limited facilities such as the number of technological devices, dependence on electricity, and students’ limited ability to operate technology-based media